2010
DOI: 10.1186/1757-7241-18-8
|View full text |Cite
|
Sign up to set email alerts
|

Risk scoring systems for adults admitted to the emergency department: a systematic review

Abstract: BackgroundPatients referred to a medical admission unit (MAU) represent a broad spectrum of disease severity. In the interest of allocating resources to those who might potentially benefit most from clinical interventions, several scoring systems have been proposed as a triaging tool.Even though most scoring systems are not meant to be used on an individual level, they can support the more inexperienced doctors and nurses in assessing the risk of deterioration of their patients.We therefore performed a systema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
88
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(90 citation statements)
references
References 29 publications
1
88
0
1
Order By: Relevance
“…However, according to the literature, none of these scoring systems has reached the highest level of evidence. [2] In many studies, it has been reported that the disorder present before arrest has an effect on survival. [4,5] However, there is no scoring system used in the prediction of mortality in CB patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, according to the literature, none of these scoring systems has reached the highest level of evidence. [2] In many studies, it has been reported that the disorder present before arrest has an effect on survival. [4,5] However, there is no scoring system used in the prediction of mortality in CB patients.…”
Section: Discussionmentioning
confidence: 99%
“…Some present without signs of organ dysfunction, while others have multiple organ dysfunction at admission but do not require ICU transfer. The severity scores used in emergency departments worldwide to categorize patients at admission all depend on clinical information such as vital signs, including altered mental state and laboratory values [2]. This information was missing from Belforti et al's study.…”
mentioning
confidence: 44%
“…Several algorithms have been developed to predict patient outcome in different settings, such as the ICU or the general ward. Algorithms developed for use in the ED are either based on data from very small or restricted groups of patients, such as medical or elderly patients, or based on elaborate laboratory tests or serial measurements [5][6][7][8][9][10][11][12][13][14][15][16][17]. These studies find level of consciousness, systolic blood pressure and respiratory frequency to be good indicators of later clinical deterioration and/or need for intensive care [8,10,14,15,17].…”
Section: Introductionmentioning
confidence: 99%